2014
DOI: 10.1007/s00381-014-2587-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DTI tractography on surgical planning for resection of a pediatric pre-pontine neurenteric cyst: a case discussion and literature review

Abstract: We report a case of a four-year-old male who presented with symptoms of brainstem compression and lower cranial nerve neuropathies. MRI revealed a large, pre-pontine mass causing brainstem compression with an uncertain intra-axial component. Using diffusion tensor imaging (DTI) tractography and other imaging modalities, we were able to confirm that the lesion was extra-axial and did not involve the corticospinal tracts. In addition, DTI tractography illustrated that corticospinal tracts were displaced to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In fetal life, the neurenteric canal establishes a temporary communication between the yolk sac and the amniotic cavity, and possibly maintains equal pressures in the 2 cavities. 27 CM-3.5 may be due to the persistence of the neurenteric canal with resultant abnormal communication between the yolk sac and the amniotic cavity. 15…”
Section: Pathophysiology Of Cmsmentioning
confidence: 99%
“…In fetal life, the neurenteric canal establishes a temporary communication between the yolk sac and the amniotic cavity, and possibly maintains equal pressures in the 2 cavities. 27 CM-3.5 may be due to the persistence of the neurenteric canal with resultant abnormal communication between the yolk sac and the amniotic cavity. 15…”
Section: Pathophysiology Of Cmsmentioning
confidence: 99%
“…During normal vertebral development, the proximal part of the axial canal of the notochord persists for a short time, allowing for a temporary communication between amniotic and yolk sacs. This canal could contribute to equalizing the pressures between the two sacs until the canal seals shut (Birinyi et al, ). Failure of this canal to close is probably involved in the anomalous neurenteric fistula seen in CM3.5.…”
Section: Chiari Malformation 35mentioning
confidence: 99%
“…25 For these reasons, DTI remains, to date, the most used technique for investigating white matter bundles, also for the pre-surgical planning of brain neoplasms. [26][27][28] In reality, as recently highlighted by Mormina and colleagues, 29 CSD-based tractography is feasible in clinical settings and it is able to provide very useful information during the pre-surgical evaluation of eloquent bundles in patients with high-grade gliomas. It was shown that DTI-based reconstructions can be affected also by neoplasm's effects on white matter bundles.…”
mentioning
confidence: 99%